Evaluation of Stress and Coping Mechanisms Among Admitted Patients’ Attendants - Aslam, Faiqa; Sarwar, Misbah; Arif, Sadaf; Rasheed, Sehrish (Biological and Clinical Sciences Research Journal, 2025)
In Pakistan, caregivers of hospitalized patients—typically family members—play a vital role in managing patient needs, but often do so at the cost of their psychological well-being. Cultural expectations, limited institutional support, and emotional strain place these attendants at increased risk of stress and poor coping outcomes. Objective: This study aimed to evaluate the levels of stress and the coping mechanisms utilized by attendants of hospitalized patients in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted at Services Hospital, Lahore, over six months from September 2024 to February 2025. A total of 40 attendants aged 25 to 60 years were selected using convenience sampling. Data were collected using a structured, validated questionnaire based on the Perceived Stress Scale (PSS) and Connor-Davidson Resilience Scale (CD-RISC). Descriptive statistics were used to analyze demographic variables, stress levels, and coping capabilities. Results: The mean age of participants was 36.85 ± 1.60 years, with females representing 57.5% of the sample. The most common stressors included fear of patient death (97.5% very stressful) and absence at the time of death (77.5% very stressful). While 37.5% of attendants reported mild stress, 27.5% experienced very high stress. Most respondents (60%) displayed moderate coping capabilities, while only 7.5% showed strong to very strong resilience. Coping strategies such as adaptability and emotional self-regulation were employed inconsistently, with a majority responding "sometimes" to coping behavior items. Conclusion: The study highlights a high burden of psychological distress among patient attendants in Pakistani hospitals, with most utilizing only moderate or inconsistent coping strategies. Targeted interventions such as psychological counselling, communication training, and structured support programs are essential to mitigate stress and enhance coping outcomes among caregivers in critical care environments.